Mulla Jewan’s Methodology in Qur'an Interpretation in the Light of Qur'an Sciences Studies (Journal of the College of Education for Women, 2020)
The importance of the interpretation of the Holy Qur’an is that it is a necessity that accompanies Muslim throughout his life, it helps him to solve his problems, it is a way of gaining advanced knowledge, it facilitates the Muslim's understanding of the Holy Qur’an and to know God’s Almighty’s intent in His verses. Since there are so many needs that a person strives to achieve, therefore, the interpretation of the Holy Qur'an would be satisfactory to him and it facilitates the fulfillment of these needs within the limits of legal laws. The aim of the researcher is to get acquainted with the method of that honoured interpreter in his interpretation, and his ability to benefit Muslims in explaining the verses and come to a solution of the problems that appear in the Muslim's life. During searching Jewan's interpretation, the researcher reaches the conclusion that he shows an interest in discussing the sciences of the Holy Qur’an, such as the reasons for descending verses, abrogater and abrogated verses, reciting, arbitrator and similar verses, and Mecca and Madeena Verses. The present research includes an introduction that contains a definition of the Holy Qur’an science, linguistically and terminologically. It consists of five sections: The first includes the reasons of the descending of the Qur’an with examples of his interpretation; the second is about abrogater and abrogated verses with a linguistic and idiomatic definition.......